C-C couplings: Organometallic reactions in water - Seßler, Miriam; Schatz, Jürgen (Chemie in Unserer Zeit, 2012)
Water has attracted significant attention as an alternative solvent for organometallic reactions because it is nontoxic, nonflammable, and inexpensive, and is easily separated from organic products. Organometallic reactions, like the palladium-catalyzed couplings of organic halides with organoboron compounds (Suzuki) and organotin reagents (Stille), are among the most widely used reactions for the formation of carbon-carbon bonds. Owing to the discovery of water-soluble, sulfonated phosphane derivatives and particularly the design of water-soluble palladium-catalysts it was possible to import these reactions into aqueous media. Another efficient, metal-catalyzed, carbon-carbon bond-forming process that is nowadays possible in aqueous media is the olefin metathesis. The approaches so far include the use of water-soluble ruthenium-catalysts, surfactants and additives, ultrasonication, the introduction of polar quaternary ammonium groups or the incorporation of PEG as a water solubilizing moiety. The last point bears also a great potential for further developments in the removal of ruthenium-containing byproducts. Additionally, water is the ideal reaction environment for polar, water soluble substrates such as natural product or pharmaceuticals. Copyright © 2012 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Combination of olefin metathesis and enzymatic ester hydrolysis in aqueous media in a one-pot synthesis - Tenbrink, Katharina; Seßler, Miriam; Schatz, Jürgen; Gröger, Harald (dvanced Synthesis & Catalysis, 2011)
A new synthetic method for the preparation of cyclic malonic acid monoesters in aqueous media was developed based on the combination of a metathesis reaction and subsequent biocatalytic hydrolysis with a pig liver esterase in a one-pot synthesis. Both reaction steps proceed smoothly under optimized conditions in aqueous media requiring only a low amount of the metal catalyst for the metathesis reaction. Notably, the applied biocatalyst turned out to be highly compatible with the metal catalyst showing no significant influence on the enzyme activity. Copyright © 2011 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Metathesis in pure water mediated by supramolecular additives - Brendgen, Thomas; Fahlbusch, Tilmann; Frank, Markus; Schühle, Daniel T.; Seßler, Miriam; Schatz, Jürgen (dvanced Synthesis & Catalysis, 2009)
Supramolecular, water-soluble additives based on calix[n] arenes exhibit a beneficial influence on the ring-closing and cross metathesis of non-polar substrates in pure aqueous medium using standard Grubbs-II and Hoveyda-II catalysts. The catalytic activity observed in water is virtually the same as that in pure methanol. Quantitative yields of metathesis product can be achieved under mild aerobic conditions in/on water by (micro)solubilization of both the catalyst and starting materials by the macrocycles. © 2009 Wiley-VCH Verlag GmbH & Co. KGaA.

Olefin metathesis reaction in water and in air improved by supramolecular additive - Tomasek, Jasmine; Seßler, Miriam; Gröger, Harald; Schatz, Jürgen (Molecules, 2015)

Product Class 9.10.4: Thiophenes, Thiophene 1,1-Dioxides, and Thiopene 1-Oxides (update) - Schatz, Jürgen; Seßler, Miriam (Thieme Verlag, 2011)

Product Class 9.11.4: Selenophenes (update) - Schatz, Jürgen; Seßler, Miriam (Thieme Verlag, 2010)

Product Class 9.12.4: Tellurophenes (update) - Schatz, Jürgen; Seßler, Miriam (Thieme Verlag, 2010)